Customer Awareness and Satisfaction of Local Islamic Banks in Malaysia - Ahmad, Shahrizan Adzham; Al-Aidaros, Al-Hasan (UUM Press, 2017)
This article explores the awareness and satisfaction of Islamic bank customers in Malaysia with respect to the banks marketing practices and effectiveness which differentiate them from conventional banks. It explores the satisfaction of customers of Islamic banks through the customers perception of the quality of the banks products and services. This study was conducted in response to pessimistic feedbacks about Islamic banks business operations which are not only required to comply with conventional business laws, but also need to give up any business prospects that are against with Shariah (Islamic law). Thus, it is argued that the marketing and advertising strategies of Islamic Banks face restricting guidelines which makes competition with their conventional counterparts (conventional banks) harder. Nevertheless, Islamic banks are strengthening their position by creating greater acceptance of their products among Muslims and Non-Muslims. Based on the descriptive analysis conducted using the data collected from a questionnaire survey of 400 respondents, this study found that a majority of the respondents are already customers of Islamic banks but they are not fully conversant with the principles of Islamic banking. The findings suggest that Islamic banks have to pay greater attention to measuring their marketing effectiveness and customer satisfaction so as to remain relevant in the marketplace.